Influence of (Non) Observance of Maxims on Evasion in Malaysian Parliamentary Question Time - Najah Zainal Abidin; Jariah Mohd Jan (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
This content-analytic study examines the influence of (non) observance of maxims in the production of evasive responses in Malaysian Parliamentary Question Time. The analysis was based on the theories of Cooperative Principle (Grice, 1975) and Clayman’s Framework of Resistance (2001; 2012). Two strategies of (non) observance of maxims were found to produce evasive responses namely, violating and opting out. Ministers and deputy ministers were found to frequently shift tasks required by providing assurances to the questioners and audience. They also acknowledged the issues raised without addressing them. Further, they talked about prior actions taken to address current issues and made a reference to another party to relieve themselves from bearing the responsibility alone which led to the violation of maxims that subsequently produced evasive responses. Evasive responses also occurred when ministers and deputy ministers disregarded the questions altogether, thus opting out of the Cooperative Principle. Despite being evasive, equivocal responses were deemed cooperative as no instances of follow-up questions were recorded.